HTT350: Tour Planning and Design / Faculty of Hotel and Tourism Management - UiTM, Faculty of Hotel and Tourism Management (2023)
The course is designed as part of the four areas of specialization within the Travel & Tour Management. It is intended for the individuals who wish to develop their practical operational skills and gain a base for pursuing a career in the travel and tour industry. Considering the changing role of the tour company in an environment of consolidation and globalization, the course provides a solid foundation for understanding all of the elements that are found in a successful tour. The step-by-step and how-to-approach tour operations allow the students to see how things are accomplished rather than simply providing theories.